Mechanical seeders to save labor for direct seeded rice in the lowland and upland of Madagascar - CGIAR Research Program on Rice (2021)
Three types of seeders were tested on-station and on-farm in Madagascar. In 2018, the small-scale equipments were demonstrated to 222 farmers and their opinions were collected to further improvement. The three seeders were further improved and tested in the 2019-2020 cropping season in Madagascar.